2001
DOI: 10.1016/s0925-4927(01)00109-3
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex, negative symptoms, and schizophrenia: an MRI study

Abstract: The present study measured prefrontal cortical gray and white matter volume in chronic, male schizophrenic subjects who were characterized by a higher proportion of mixed or negative symptoms than previous patients that we have evaluated. Seventeen chronic male schizophrenic subjects and 17 male control subjects were matched on age and handedness. Regions of interest (ROI) were measured using high-resolution magnetic resonance (MR) acquisitions consisting of contiguous 1.5-mm slices of the entire brain. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(120 citation statements)
references
References 69 publications
15
100
0
5
Order By: Relevance
“…This suggests that auditory impairment in schizophrenia extends beyond the superior temporal gyrus and Heschl's gyrus as shown in earlier fMRI studies, 10,24,25 and as inferred from event-related potential studies of the auditory mismatch negativity. 26 Impaired thalamic function has been reported in controlled processing, 4 but not in automatic processing.…”
Section: Functional Changes In Schizophrenia With Automatic Processingsupporting
confidence: 57%
“…This suggests that auditory impairment in schizophrenia extends beyond the superior temporal gyrus and Heschl's gyrus as shown in earlier fMRI studies, 10,24,25 and as inferred from event-related potential studies of the auditory mismatch negativity. 26 Impaired thalamic function has been reported in controlled processing, 4 but not in automatic processing.…”
Section: Functional Changes In Schizophrenia With Automatic Processingsupporting
confidence: 57%
“…These studies together suggested that normal white matter myelination with increasing age is abnormal in patients with schizophrenia. White matter atrophy in the frontal lobes has been noted in other recent studies (Sanfilipo et al, 2000;Wible et al, 2001), but the discrepancy may be due to not taking the normal aging process into account.…”
Section: Cortical Development and Schizophreniamentioning
confidence: 76%
“…The negative symptoms of schizophrenia have in some studies been correlated with prefrontal dysfunction, and with extensive gray and white matter abnormalities in cortico-thalamo-cortical circuits (Gur et al, 2000;Lieberman et al, 2001;Mathalon et al, 2001;Nopoulos et al, 2001;Paillere-Martinot et al, 2001;Sigmundsson et al, 2001;Wible et al, 2001). Few clinical studies have specifically explored the biological basis of social dysfunction in schizophrenia, but one study suggests that morphological abnormalities of the ventral frontal cortex could be connected to social dysfunction (Chemerinski et al, 2002).…”
Section: Social Interactionmentioning
confidence: 99%